2003
DOI: 10.1093/emboj/cdg073
|View full text |Cite
|
Sign up to set email alerts
|

H+/ATP ratio of proton transport-coupled ATP synthesis and hydrolysis catalysed by CF0F1-liposomes

Abstract: The H + /ATP ratio and the standard Gibbs free energy of ATP synthesis were determined with a new method using a chemiosmotic model system. The puri®ed H + -translocating ATP synthase from chloroplasts was reconstituted into phosphatidylcholine/phosphatidic acid liposomes. During reconstitution, the internal phase was equilibrated with the reconstitution medium, and thereby the pH of the internal liposomal phase, pH in , could be measured with a conventional glass electrode. The rates of ATP synthesis and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
129
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 41 publications
(50 reference statements)
6
129
1
Order By: Relevance
“…When the ΔpH was abolished by addition of 10 μM nigericin, CF 0 F 1 and MF 0 F 1 showed different responses: CF 0 F 1 did not show any ATP hydrolysis, whereas MF 0 F 1 did. This is in agreement with previous results (18,19) and confirms that CF 0 F 1 is a strongly regulated enzyme, which is inactive in the absence of a pre-energization by Δμ H þ (23). We concluded that CF 0 F 1 did not catalyze uncoupled ATP hydrolysis and that, therefore, no corrections for uncoupled ATP hydrolysis were required.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…When the ΔpH was abolished by addition of 10 μM nigericin, CF 0 F 1 and MF 0 F 1 showed different responses: CF 0 F 1 did not show any ATP hydrolysis, whereas MF 0 F 1 did. This is in agreement with previous results (18,19) and confirms that CF 0 F 1 is a strongly regulated enzyme, which is inactive in the absence of a pre-energization by Δμ H þ (23). We concluded that CF 0 F 1 did not catalyze uncoupled ATP hydrolysis and that, therefore, no corrections for uncoupled ATP hydrolysis were required.…”
Section: Resultssupporting
confidence: 93%
“…To apply this method we constructed a minimal chemiosmotic system (18,19). Liposomes from phosphatidylcholine/phosphatidic acid were prepared, and either the chloroplast or the mitochondrial enzyme was reconstituted into the liposome membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the reported number of c subunits in the chloroplast enzyme (52) is correct, the proton/ATP stoicheiometry should be 4.67 (14 divided by 3) according to the current rotational model (rotation of the ring of c subunits is coupled with the passage of one proton through each of the c subunits and with rotation of the g subunit without slip), while this number has been determined as being 4.0 (53,54). A movement over 120 degrees, however, can accommodate this number quite well.…”
Section: Structural Evidencementioning
confidence: 99%